Prevalence of Vitamin A Deficiency among Malnourished Children in Usmanu Danfodiyo University Teaching Hospital, Sokoto, Northwestern Nigeria - Adamu, A.; Jiya, N.M.; Ahmed, H.; Ibitoye, P.K.; Ugege, M.O.; Sani, U.M.; Yusuf, T.; Jiya, F.B.; Isezuo, K.O. (Pakistan Journal of Nutrition, 2016)
Malnutrition refers to a group of pathological disorders resulting from imbalance between intake of essential nutrients and body requirement for these nutrients. It is classified broadly into macronutrient and micronutrient malnutrition. The former comprises Protein energy malnutrition (PEM) and over nutrition/obesity, while the latter encompasses specific micronutrient deficiencies such as vitamin A, zinc (Zn), iodine etc. Micronutrient deficiencies are less dramatic in manifestation and frequently not recognised. Vitamin A deficiency (VAD) is a public health problem affecting 5% of population in developing countries of the world. The study is relevant as it seeks to provide local data on this subject. This study was conducted to determine the prevalence of vitamin A deficiency among children with malnutrition and to compare serum vitamin A levels between children with malnutrition and age matched well-nourished children. A total of 550 children, 275 with malnutrition and 275 controls, aged 6 months to 60 months that satisfied the inclusion criteria were recruited at various Paediatric units of Usmanu Danfodiyo University Teaching Hospital (UDUTH), Sokoto after parents and caregivers consented in writing. Serum vitamin A was analysed using colorimetric method of Bassey. The mean serum level of vitamin A in malnourished children was 23.4±13.2 μg/dl which was significantly lower when compared to that of the controls 54.1±22.8 μg/dl, respectively (p = <0.05). The prevalence of VAD was 8.4% among children with malnutrition and 4.0% among the control cohorts, respectively. It was concluded that children with malnutrition had significantly lower serum vitamin A level compared to the controls.